Validation of the formation rate of growth rings in otoliths of Jack mackerel Trachurus murphyi Nichols 1920 - Goicochea, Carlos (2013)
We present the results of the validation of Jack mackerel Trachurus murphygrowth with three techniques: 1) validation of the first annual ring by reading daily microincrements; 2) analysis of the growth of the otolith radius between the second and third ring, following-up one cohort; and, 3) conventional interpretation of annual rings. The results show that the average age of Jack mackerels T. murphyiwith the first fully formed ring was 364.8 days, with a mean total length of 19.5 cm, and that the increment from the second to the third ring is on average 0.62 mm. The estimated growth parameters were L oo = 75.17 cm, k= 0.165 /year, t o = -0.817 year. These results are discussed, highlighting that the Peruvian Jack mackerel T. murphyiappears to grow faster than Chilean Jack mackerelT. murphyi. The radius of the first annual ring is up to 18% larger than reported by other authors for the Chilean Jack mackerel, while the radius of the otoliths of two and three year-olds was up to 20% higher. Also the average length of a one year old Peruvian Jack mackerel is approximately 35% larger than that of the Chilean Jack mackerel, obtained by other authors. The growth index phi prime (Ø') estimated for the Peruvian Jack mackerel in this study and others show similar growth patterns, given the low value of the coefficient of variation (1%), lower than the (7%) reported by others authors for the more southern Jack mackerel T. murphyi.